Quality of life and late‐effects among childhood brain tumor survivors: a mixed method analysis. Issue 6 (5th October 2015) - Gunn, Mirja Erika; Mört, Susanna; Arola, Mikko; Taskinen, Mervi; Riikonen, Pekka; Möttönen, Merja; Lähteenmäki, Päivi Maria
Abstract: Background: Reports on the quality of life (QOL) of childhood brain tumor (BT) survivors have been inconsistent. As cognitive limitations may restrict their participation in questionnaire‐based studies, our aim was to evaluate in depth the QOL with a mixed‐method analysis. Methods: The 5‐year survivors of childhood BTs born in 1975–2000 and alive in 2010 were identified via the Finnish Cancer Registry and treating clinics. Twenty‐one survivors (32%) participated in a mixed‐method analysis including 15D (a general health‐related QOL questionnaire), the Beck Depression Inventory, and a qualitative semi‐structured interview. Results: Based on the 15D‐questionnaire, the BT survivors had an impaired health‐related QOL in several dimensions such as speech and usual activities. On the other hand, no difference was found in other dimensions such as distress or vitality. A majority (95%) of the survivors showed no increased risk for depression. The qualitative interview revealed that the most important aspects affecting the QOL of the survivors were positive mental growth, negative conceptions concerning illness, living one day at a time, age at diagnosis, time since diagnosis, social relationships, learning disabilities and limitations in vocational opportunities, limitations in independent life, and changed understanding of the term 'health'. Conclusions: Childhood BT survivors have heterogeneous attitudes on QOL. The survivors assess social aspects to be more important than functionality for their QOL. Social concerns should actively be brought up to offer support for those with significant social difficulties. Interventions for social difficulties should be more actively developed. Copyright © 2015 John Wiley & Sons, Ltd.